Sociodemographic profiles and diagnostic patterns of prisoners admitted to a tertiary care psychiatric hospital - Uzma Viquar; P. C. B. Gupta; Rajeevi Keeta (Telangana Journal of Psychiatry)
Background: Most of the studies were performed on patients staying in prisons. This study is conducted on prisoners admitted to a psychiatric hospital. This study attempts to understand the interwoven multiple and complex problems. Aim: This study aims to study the sociodemographic profiles and diagnostic patterns of prisoners admitted to a tertiary care psychiatric hospital. Materials and Methods: After obtaining institutional ethics committee approval, intake pro forma was obtained from convenient sample of 50 patients fulfilling inclusion criteria. The diagnosis was done based on the International Classification of Diseases 10; the International Personality Disorder Examination Scale was applied for personality assessment. Settings and Design: This was a cross-sectional study in a hospital setting. Statistical Analysis: The results obtained were subjected to statistical analysis using SPSS version v 27.0. Results: The majority of the subjects were aged between 26 and 35 years and were married; major proportion were illiterate and unemployed. The most common complaints were sleep disturbances followed by hearing of voices. A history of substance use in the family was observed in a vast proportion of the cases. Family history of psychiatric illness and childhood history of bullying, lying, stealing, and truancy were found in many prisoners. The most common diagnosis was found to be schizophrenia. Conclusions: Most of the prisoners directed to the psychiatric hospital were young adults in their most productive age, and their psychiatric morbidity is a result of multiple factors. They need to be timely screened and followed up regularly in psychiatric settings.